A Comparative Analysis of English Discourse Markers in British and American Football Commentary - Pradana Ajiasa, Mokhammad; Rahayu Puji Haryanti; Issy Yuliasri (English Education Journal, 2024)
There are plenty of ways to utilise discourse in the field of language, for example in football commentary. It is natural, unplanned, free of scripts, and spontaneous. However, football discussion and commentary differ significantly from regular speech. The aim of this study is to compare the use of English discourse markers in sport-casting or football commentary by the British and American football commentators. This study used a qualitative study. The data were collected through a spoken discourse analysis from two (2) football match videos produced by British and American football commentators, which were transcribed into a text analysis and then determined the functions, types, and frequency of discourse markers. The finding showed that British commentators used discourse markers more frequently than the American commentators.